2011
DOI: 10.1007/s00784-011-0593-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation on porcelain laminate veneers bonded with light-cured composite: results up to 7 years

Abstract: The purpose of this study was to evaluate the clinical performance of laminate porcelain veneers bonded with a light-cured composite. Thirty patients were restored with 119 porcelain laminate veneers. The veneers were studied for an observation time of 7 years. Marginal adaptation, marginal discoloration, secondary caries, color match, and anatomic form were clinically examined following modified United States Public Health Service (USPHS) criteria. Each restoration was also examined for cracks, fractures, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 22 publications
3
104
0
11
Order By: Relevance
“…8,9,[15][16][17] Konservatif tedavi seçeneğinin uygulanması restorasyonun uzun dönem başarısı için olumlu bir yaklaşımdır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…8,9,[15][16][17] Konservatif tedavi seçeneğinin uygulanması restorasyonun uzun dönem başarısı için olumlu bir yaklaşımdır.…”
Section: Discussionunclassified
“…Venerler, hem biyouyumlu hem de estetik olmalarından dolayı ön grup restorasyonlar da tercih edilmektedir. [15][16][17][18][19] Bu olgu sunumunda basit ön açık kapanışı olan bir kadın hastada, estetik ihtiyacı karşılamak için planlanan tedavi yaklaşımı ve tedavinin üç yıllık takip sonuçları anlatılmaktadır.…”
Section: Open-bite Dental Veneers Gingivoplastyunclassified
“…However, the result of the robotic tooth preparation system showed a significantly higher level of both accuracy and precision at the finish line. The preparation of the finish line is most challenging and critical for the long-term clinical success of PLVs because of the limited amount of enamel in the cervical area 8,11,12 and the risk of traumatizing gingival tissue. These results suggest that the application of robotic technology for tooth preparation for PLVs is beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Multiple clinical studies have demonstrated that when PLVs are bonded to enamel (at least 50% bonding surface is enamel) and when the finish-line is placed supragingivally on enamel, these restorations are extremely successful. [7][8][9][10] The enamel thickness of anterior teeth varies according to area and tooth type. 11,12 Clinically, the average enamel thickness has been used as one of the references for the tooth preparation of PLVs.…”
Section: Research and Educationmentioning
confidence: 99%
“…Porselen lamina restorasyonların klinik başarısını değerlendiren ça-lışmalar olmasına rağmen, parsiyel laminate ile ilgili dental literatürde henüz orta ve uzun dönemli klinik çalışma bulunmamaktadır. 10 Bu nedenle kanin dişle-rin restorasyonu direkt yöntemle kompozit rezin uygulanarak gerçekleştirilmiştir.…”
Section: Discussionunclassified